Determinants of employee engagement in Honda Malaysia Sdn. Bhd. - Ayuni Asma, Abdullah (2016)
Engaged employees will say positive things about the company, give extra effort, and are more likely stay with their company. Therefore, it is not surprising that most of organizations have invested substantially in policies and practices that foster engagement and commitment in their workforce. This study examined the relationship between rewards & recognition, career development, flexible working hours and employee engagement. 158 survey questionnaires were collected and used for data analysis in this study. Descriptive and inferential statistics were employed to analyse data. The findings showed that there were significant and positive correlations between rewards & recognition, career development, flexible working hours and employee engagement. Findings also indicated that career development was the most dominant determinant of employee engagement in Honda Malaysia Sdn. Bhd. ("HMSB"). The research findings will help to gain a better understanding and insight into what drives employee engagement in HMSB.